Effect of lipid supplementation on milk fatty acid focus on rumenic acid. - Prieto-Manrique, Esperanza (2016)
The aim of this study was to review the effect of the lipid supplementation on the concentration of conjugated linoleic acid (CLA-c9t11) or rumenic acid and other unsaturated fatty acids in bovine milk. The study addressed the concept and origin of the CLA-c9t11 in ruminants. There is an international trend to improve nutrition quality , which implies an increase in consumption of animal protein, including the healthy and rich in CLA-c9t11 dairy products. CLA-c9t11 has proved to have anticancer effects in animal models. CLA-c9t11 in the bovine milk results from the consumption of unsaturated fatty acids and from the extent of rumen biohydrogenation. Supplementation with unsaturated fatty acids of vegetable origin allows to increase the concentration of CLA-c9t11 and to decrease the proportion of saturated fatty acids in milk, but the response varies depending on the source of fat used, its level, and its interaction with basal diet.